Legal Liability Of Business Actors In Indonesia - Alvin Hairi; Taufiqur Rahman; Aldi Atmanegara; Sultan Diyas; Fadhil Daifullah; Roland Anggala Perdana; Adi Fitra Andikos (The Future of Education Journal, 2025)
This study aims to analyze the legal liability of business actors in Indonesia within the existing legal framework, including the Consumer Protection Law, Civil Law, and Criminal Law. The research employs a qualitative approach with a case study method to explore in depth various violations involving business actors. Data were collected through in-depth interviews with legal experts, legal document analysis, and case studies from court reports. The findings indicate that the legal liability of business actors in Indonesia covers both civil and criminal aspects, focusing on consumer protection, contractual obligations, and the prevention of negative impacts on society and the environment. However, the implementation of such responsibilities is often hindered by weak law enforcement, low consumer legal awareness, and power imbalances between business actors and affected parties. This study recommends strengthening regulations, raising legal awareness, and fostering synergy among supervisory institutions to ensure that the legal liability of business actors is effectively enforced.